Oxygen uptake, heart rate and lactate during endurance training in top class rowers - Hartmann, U.; Mader, A. (Medicine & Science in Sports & Exercise, 1996)
In 12 elite German males it was shown that three hours of rowing per day can only be completed at a very low level of intensity with only a few high intensity loads. This leads to a training of about 55-60% of the total training or 85-94% of on-the-water training with an intensity of less than 2 mM lactate. Implication: Most rowing training will be at a low effort demand and will produce non-race-specific aerobic adaptation. When speed and more anaerobic work is required an emphasis will have to be placed on recovery otherwise excessive overloading will result. The capacity of rowers to work "hard" seems to be less than is popularly espoused.